2021
DOI: 10.21203/rs.3.rs-948389/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Biodegradable Reduce Expenditure Bioreactor For Augmented Sonodynamic Therapy Via Regulating Tumor Hypoxia And Inducing Pro-Death Autophagy

Abstract: Backgrounds: Sonodynamic therapy (SDT) as an emerging reactive oxygen species (ROS)-mediated antitumor means is still hampered by the rapid depletion of oxygen, as well as hypoxic tumor microenvironment. Instead of the currently coping strategies through amplifying endogenous O2 level, herein, a biodegradable O2 economizer is described as a reduce expenditure bioreactor for augmenting SDT efficacy. Results: We have successfully fabricated the O2 economizer (HMME@HMONs-3BP-PEG, HHBP) by the conjugation of respi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…org/ 10. 1186/ s12951-021-01166-y Following publication of the original article [1], the authors identified an error in Fig. 6d.…”
mentioning
confidence: 99%
“…org/ 10. 1186/ s12951-021-01166-y Following publication of the original article [1], the authors identified an error in Fig. 6d.…”
mentioning
confidence: 99%